Embracing Choice and Abandoning the Ballot: Lessons from Berkeley's Popular Defeat of Sit-Lie - Oxsen, Courtney (2014)
In November 2012, Berkeley voters defeated Measure S, an ordinance that would have made it illegal to sit down in Berkeley's commercial districts during most of the day, a so-called sit-lie law. Sit-lie laws have become increasingly prevalent nationwide as a means to combat the presence of homeless individuals in downtown areas, ever since Seattle's sit-lie regulation was upheld by the Ninth Circuit Court of Appeals in 1996. Debate over the efficacy and constitutionality of sit-lie laws has been fierce nationally and in individual localities. Proponents of the measure say sit-lie laws are a necessary tool for law enforcement to maintain order in public spaces, protect local economies and community members, and usher homeless people into public services. Opponents counter that such laws are inhumane towards homeless individuals, ineffictive as a solution to the crisis of homelessness in the United States or the economic woes of local business, and meant only to hide the homeless from view and preserve the comfort of the fInancially priveleged. This Note contextualizes Measure S within a larger framework of the sit-lie movement nationwide and explicates a proposal with applicable lessons from from Berkeley's experience for municipalities, sit-lie proponents, and homelessness advocates facing the potentiality of a sit-lie measure and continued community discussion in their locality